2014
DOI: 10.1108/sasbe-05-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation framework for green procurement in road construction

Abstract: Purpose – Most barriers and enablers of sustainable projects are related to procurement. The purpose of this paper is to propose a framework for evaluating green procurement practices throughout the lifecycle of road construction projects and demonstrates its application through an Australian case study. Design/methodology/approach – The study is based on linking the phases of road construction with incentive mechanisms for proactively m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
1
19
0
8
Order By: Relevance
“…The greater the pressure on employees within the enterprise is, the higher the tendency to GP. Additionally, this rule is also prevalent in the construction industry of the United States [83], the United Kingdom [45] and Australia [84]. However, the research found that the actual internal pressure on employees in Chinese real estate enterprises is not great and thus the degree of implementation of GP in real estate enterprises is not high.…”
Section: Management Implicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…The greater the pressure on employees within the enterprise is, the higher the tendency to GP. Additionally, this rule is also prevalent in the construction industry of the United States [83], the United Kingdom [45] and Australia [84]. However, the research found that the actual internal pressure on employees in Chinese real estate enterprises is not great and thus the degree of implementation of GP in real estate enterprises is not high.…”
Section: Management Implicationsmentioning
confidence: 96%
“…Actually, this problem is common in many developing and developed countries. For example, Kiron et al [84] conducted a worldwide survey of the sustainable development of enterprises, finding that construction companies generally did not focus on formulating policies to encourage employees and partners to make a positive response to environmental issues.…”
Section: Management Implicationsmentioning
confidence: 99%
“…o Penalty and Payment calculations: The amount of a Penalty (Pe) is calculated by using Eq. (23). Also, the project payment (Pa) which is calculated according to Eq.…”
Section: Cep Bidding Methodsmentioning
confidence: 99%
“…This established strategy shows that the owner also ready to adapt their performance conditions to alteration context. Adriana et al [23] proposed a green procurement framework for evaluating a contractor of a road construction project in Australia. This is based on interviews and procurement documents across five Australian states.…”
Section: Green Public Procurement For Construction Projectmentioning
confidence: 99%
See 1 more Smart Citation